Political Image Strategy on TikTok: A Case Study of 'Gemoy' - Serly Novita Juliantari; Anang Sujoko; Maulina Pia Wulandari (Universitas Muhammadiyah Malang, 2025)
This research examines the visual image-based political communication strategy on the TikTok platform by highlighting the “gemoy” symbol as part of a political campaign aimed at the younger generation. This phenomenon shows a shift in the way political messages are delivered from a rational-informative approach to an affective-visual approach that utilizes popular culture. The main problem in this research lies in how political meaning is formed through the symbolization of the “gemoy” image and to what extent it affects young people's political involvement. The purpose of this research is to identify the various meanings of young audiences towards image-based political communication and explain the dynamics of symbol meaning in the context of digital culture. The method used is a qualitative approach with a case study, relying on data collection techniques in the form of in-depth interviews, observation of TikTok content, and visual documentation. Data were obtained from interactions with TikTok users aged 17-25 as well as analysis of political content using the “gemoy